Study of Uni-Bivalent Ion Exchange Equilibria in Cl-/SO42- System using Strongly Basic Anion Exchanger Amberlite IRA-400 - Lokhande, R.S.; Singare, P.U. (Asian Journal of Chemistry, 2010)
Ion exchanger in chloride form was allowed to reach equilibrium with sulphate ion solution of seven different concentrarions from 0.010 M to 0.050 M and the equilibrium concentration of the chloride and sulphate ions in the solution was determined. From the knowledge of ion exchange capacity of the resin, the amounts of the chloride and sulphate ions in the resin phase were calculated. From these results, the apparent equilibrium eonstants (Kapp) for the system, the ratio of the activity co-efficients of ions in the resin phase and hence the standard equilibrium constant (Kstd) were calculated. The value of Kstd. increases from 20 at 30oC to 31 at 45°C, indicating the endothermic ion exchange reaction. From the knowledge of standard equilibrium constants at different temperatures, enthalpy of ion exchange reaction was calculated to be 11.5 kJ/mole.